Updated aspects of alpha-Solanine as a potential anticancer agent: Mechanistic insights and future directions - Nandi, Sudeshna; Sikder, Rimpa; Nag, Anish; Khatua, Somanjana; Sen, Surjit; Chakraborty, Nilanjan; Calina, Daniela (Wiley, 2024)
Cancer remains a critical global health challenge, with limited progress in reducing mortality despite advancements in diagnosis and treatment. The growing resistance of tumors to existing chemotherapy exacerbates this burden. In response, the search for new anticancer compounds from plants has intensified, given their historical success in yielding effective treatments. This review focuses on alpha-solanine, a glycoalkaloid primarily derived from potato tubers and nightshade family plants, recognized for its diverse biological activities, including anti-allergic, antipyretic, anti-inflammatory, anti-diabetic, and antibiotic properties. Recently, alpha-solanine has gained attention as a potential anticancer agent. Utilizing resources like PubMed/MedLine, ScienceDirect, Web of Science, Scopus, the American Chemical Society, Google Scholar, Springer Link, Wiley, and various commercial websites, this review consolidates two decades of research on alpha-solanine's anticancer effects and mechanisms against nine different cancers, highlighting its role in modulating various signaling pathways. It also discusses alpha-solanine's potential as a lead compound in cancer therapy. The abundant availability of potato peel, often discarded as waste or sold cheaply, is suggested as a sustainable source for large-scale alpha-solanine extraction. The study concludes that alpha-solanine holds promise as a standalone or adjunctive cancer treatment. However, further research is necessary to optimize this lead compound and mitigate its toxicity through various strategies.
Keywords: anticancer mechanisms; apoptosis; glycoalkaloids; Solanaceae; alpha-Solanine